Carbon nanofiber-reinforced strain sensors with high breathability and anisotropic sensitivity. Issue 47 (23rd November 2021) - Peng, Shuhua; Wu, Shuying; Yu, Yuyan; Sha, Zhao; Li, Guang; Hoang, Trung Thien; Thai, Mai Thanh; Do, Thanh Nho; Chu, Dewei; Wang, Chun H.
Abstract : In this work, we present a new method of creating fibre-metal composites to effectively modulate the in-plane fracture behaviour of brittle conductive thin metal films on stretchable PDMS substrates via insertion of a toughening interlayer of CNFs. Abstract : The direct deposition of thin metal films on highly elastic substrates is a major technique used to fabricate flexible electronics such as wearable sensors, stretchable transistors, and deformable displays. However, these devices suffer from low stretchability due to the limited ductility of the metal films. Herein, we present a new method of significantly extending the sensing range of metal film sensors by introducing nanofibers to control the growth of microcracks. This new technique overcomes the major limitation of flexible electronic devices' propensity to abrupt electrical failure caused by plastic deformation and long-channel cracks in thin metal films of low yield strain and ductility. The fibre-metal films were made by depositing metals on a flexible substrate coated with carbon nanofibers (CNFs). The resulting nanofiber-metal composite films were found to form short microcracks bridged by conductive CNFs, instead of long-channel cracks commonly found in metal films subjected to mechanical stretching. This led to an impressive increase in the sensing range, from 5% to 120% with an ultrahigh sensitivity of 417 and an excellent linearity of 97%, which are significantly higher than the reported values of microcrack-based strain sensors. A holey pattern analogous to the breathable medical tape was introduced into these strain sensors to endow them with good breathability and wearing comfort. The shape and alignment of the holes control the directional sensing capability of breathable strain sensors to detect complex human motions. The techniques presented herein offer a new route to develop next-generation flexible electronics using nanofiber-reinforced metal composite films.